A Mathematical Approach to Photosynthesis and Growth of Tree Species - Gopal, Madan (Indian Forester, 1972)
Process of photosynthesis followed by series of complex reactions results in growth of plants (trees included). Part of energy assimilated in photosynthesis is consumed through respiration. Rates of these processes are influenced by light, temperature, moisture, food supplies etc. and these conditions are largely determined by the season. The relationsbip between growth rate of trees and environmental factors is very complex. However, by adopting approximations and applying principles of physical sciences to the biochemical processes concerned with growth, seasonal growth rates under different weather conditions bave been expressed in the form of a mathematical equation. This equation helps in indicating the relative importance of various environmental factors for a speeies. It can also offer a measure of suitability of a soil for a given species. The equation has been fitted to the seasonal growth rate data of Pinus elliottii collected at Dehra Dun. Study of growth pattern of this species reveals that clear weather for at least part of summer period is a must for its good performance. The approach suggested in this paper may be applied for study of relationship between rate of CO2 assimilation in species and environmental factors.